Aplikasi Perbaikan dan Manipulasi Citra Digital Berbasis Android - Anthony Wijaya; Liliana Liliana; Anita Nathania Purbowo (Jurnal Infra, 2015)
Technology is always evolving today is the smartphone. Even today smartphone can replace a lot of the role of one of the camera or computer and have become as one of the necessities for most people. The camera of the mobile phone one of which is widely used, but sometimes the picture is still not good so the need for image enhancement. Editing application on the computer one way to fix it. But with it still less practical because many processes that must be performed. Therefore, the application of repair and manipulation of digital images based on Android it easier to make edits or changes to the image.Systems made include the process of taking pictures from external memory smartphone, insert the image into the acticty main menu editor. This menu can be selected four existing menu ie brightness, contrast, auto contrast and blur. The auto contrast using the histogram method and using the RGB and HSV color space, while for the blur, brightness and contrast using RGB color space. This application is built using the Java programming language with the android his studio as an IDE.The test results show the value or number adders and multipliers for the brightness and contrast is very influential on the final result image, because it will make the picture look even brighter or darker. Giving blur effect cannot be given once to a high level of blur due to high blur effect makes the process will be long. In the process of auto results in images that are too light will produce images that appear broken ghosting or auto process works better if the images tend to be dark, large pixels also affects the work of the editing process.